Recent advances in non-metal modification of graphitic carbon nitride for photocatalysis: A historic review - Zhou, L.; Zhang, H.; Sun, Hongqi; Liu, S.; Tade, M.; Wang, S.; Jin, W. (RSC Publications, 2016)
Photocatalysis is a green, feasible and versatile technology that has been widely used for energy conversion and environmental applications. As photocatalysis bears a great potential for solar energy utilization, enormous investigations have been implemented in the past decades. The fundamental mechanism and some applications were well addressed in the last century. Currently, the major focus in photocatalysis research is the design and development of photocatalyst materials. This review firstly introduces the historic milestones in photocatalysis studies and then a comprehensive survey is conducted on the metal-based photocatalysts, including TiO2-based photocatalysts, ZnO and other metal oxides, metal sulfides, metal nitrides, and plasmon photocatalysts. From a historical viewpoint, particular attention is paid to metal-free graphitic carbon nitride (g-C3N4), a novel visible-light photocatalyst. Various modification techniques for g-C3N4 are summarized and analyzed. In terms of its metal-free nature, the fabrication of a porous structure, shape-control synthesis and non-metal doping are discussed in detail. Photocatalytic studies on g-C3N4-based catalysts are introduced. Some emerging elemental photocatalysts are also introduced. Finally, perspectives on non-metal photocatalyst design and development are provided.